PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA PEMERINTAH DAERAH DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERATING (Studi Empiris Pada Kec. Maduran, Laren dan Sekaran Kabupaten Lamongan) - Imroatus Sholikah; Nur Hidayati; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACT             This study aims to examine: 1) the influence of budgeting participation on the performance of local governments. 2) the influence of budget participation on the performance of local governments with organizational commitment as a moderating variable. This type of research is classified into causative research. The population in this study were all budget staff in Maduran, Laren and Sekaran districts, Lamongan Regency. Sample selection using the total sampling method. Data uses primary data. Data collection techniques by distributing questionnaires to the Lurah, Head of Subdivision, Sub-district Head and Sub-district secretary. The analysis used is MRA (Moderate Regression Analysis).            The results of the study show that: 1) budgeting participation has no significant negative effect on local goverment performance (H1 rejected). 2) organizational commitment moderates the influence of budgetary participation on local goverment performance (H2 accepted).Keyword: local government performance, budget participation, organizational commitment.